Pojavne oblike memorije in spomina v literarnih delih Prežihovega Voranca - Köstler, Erwin (Jezik in slovstvo, 2010)
Prežihov Voranc is an author who in his narratives, reportage and travelogues to a large extent and on various (inter)textual levels addresses the topics of the memory and recollection. On the basis of Jan Assmann's concept of collective memory and current studies on the applicability of the concept to literary-historical methodology, with reference to selective examples the discussion treats various functions of these themes, particularly the use of mnenotope and the the body as the "place" of collective identity. There is an emphasis on the aspect of communicative memory and the connection on the author to regional cultural recollection, which comes clearly to expression in the chronotope of the journey and in the material that the author (apparently) takes from the people's oral narrative.
Keywords: 20. st.; kolektivni spomin; mnemotipi; Prežihov, Voranc; Slovene literature; slovenska književnost; slovenski pisatelji; spomini